Peran Dinas Tenaga Kerja dan Transmigrasi Provinsi Sumatera Barat dalam Manajemen Kegiatan Job Fair (Pameran Kesempatan Kerja) - Adriyan, Dendi Putra; Eriyanti, Fitri (Lembaga Yasin AlSys, 2025)
Labor absorption through Job Fair activities continues to face various challenges, particularly in non-industrial regions such as West Sumatra. This study aims to analyze the role of the Department of Manpower and Transmigration of West Sumatra Province in managing Job Fair activities and to identify the supporting and inhibiting factors in its implementation. Using a qualitative approach with a descriptive method, the research was conducted at the Department of Manpower and Transmigration of West Sumatra Province in Padang City, involving eight informants selected through purposive sampling. Data were collected through in-depth interviews, participatory observation, and documentation studies, then analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that the Department carries out four main roles in Job Fair activities: as a facilitator, educator, representative, and technical implementer. These roles are realized through the provision of facilities, employment education, cross-sectoral networking, and systematic program management. Supporting factors include effective communication and organized management, while limited company participation due to the region’s non-industrial characteristics and suboptimal promotional efforts serve as the main obstacles. This study contributes to the development of public sector role theory in employment service management and emphasizes the importance of collaborative strategies and public communication in supporting the success of Job Fair programs. Further studies are recommended to evaluate program effectiveness longitudinally and to compare Job Fair implementation in industrial and non-industrial regions to enrich the field of public employment management.